3. PREMENSTRUAL SYNDROME AND ITS RELATIONSHIP WITH SOME RISK FACTORS AMONG FEMALE STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objective: This study aimed to describe the prevalence of premenstrual syndrome (PMS) and analyze its relationship with some risk factors among female students at Hanoi Medical University in 2022.Subject and method: A cross-sectional descriptive study in all majors from the first to the sixth year of Hanoi Medical University.Results: Out of 412 study subjects, 69.9% of students had no PMS or mild PMS; 30.1% had moderate to severe PMS. Fatigue/lack of energy (89.3%) and anxiety/tension (78.2%) were the most common symptoms. Bachelor curriculum, dysmenorrhea, the amount of menstrual bleeding and total sedentary time were the associated factors with the higher severity of PMS (p
Keywords: Premenstrual syndrome, medical student, female.